Psychosocial Factors at Work and Obesity Among Young Finnish Adults: A Cohort Study. Issue 5 (May 2015) - Jääskeläinen, Anne; Kaila-Kangas, Leena; Leino-Arjas, Päivi; Lindbohm, Marja-Liisa; Nevanperä, Nina; Remes, Jouko; Järvelin, Marjo-Riitta; Laitinen, Jaana
Abstract : Objective: To examine the associations between occupational psychosocial factors and obesity among 31-year-olds, adjusting for adolescent body mass index, physical strenuousness of work, and adverse health behaviors (ie, stress-related eating/drinking, leisure-time physical inactivity, smoking, and high alcohol consumption). Methods: The study population comprised 2083 men and 1770 women from the Northern Finland Birth Cohort 1966. Obesity was defined as a body mass index of 30.0 kg/m 2 or more. Psychosocial exposures were defined in terms of demands, control, and social support at work. Results: Among men, high job demands and low worksite social support were independently associated with obesity. Among women, stress-related eating/drinking and physical inactivity seemed to promote obesity. Body mass index at age 14 was an important predictor of obesity for both sexes. Conclusions: In workplace obesity prevention programs, it might be beneficial to improve the psychosocial work environment and promote healthy behaviors simultaneously.